Hydroxamic Acids Interactions with Tin: An Overview - Abdualbasit M Graisa; Amani A Husain; Ahmed Al- Ani; Hamsa Thamer; Sarah Mahdi; Dina S Ahmed; Salam Mohammed; Emad Yousif (Fakultas Teknik, 2022)
This review focuses on the synthesis, structural study and application of hydroxamic acid (HA) and its complexes with organotin (IV) to produce organotin (IV) hydroxamate. Organotin (IV) compounds have received great attention in research field as a photostabilizer in PVC and its application in different aspect, such as marine (in anti-fouling paints and coatings for the protection of ship hulls) and as precursors for SnO2-coatings on glass and in biological field. Different studies done by researchers highlighted on the organotin (IV) complexes and its applications. This article summarize various studies on organotin(IV) complexes and their applications.